1998
DOI: 10.1080/00221329809596157
|View full text |Cite
|
Sign up to set email alerts
|

The Relation of Problem Behaviors in Preschool Children to Depressive Symptoms in Mothers and Fathers

Abstract: The relation of maternal and paternal depressive symptoms to problem behaviors in a nonclinical sample of preschool children was examined. Data were collected from 46 women, their husbands, and their 4-year-old, first-born children. Observed maternal restrictive and punishing behavior and attachment security of the child were considered additional sources of risk for externalizing and internalizing problem behaviors. Different predictors for child externalizing and internalizing behaviors were identified via h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
53
0
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 21 publications
6
53
0
2
Order By: Relevance
“…There is evidence to suggest that paternal psychological functioning, including depression and stress, is associated with externalising child behavior problems that can originate very early in development [23][24][25][26]. For example, a recent large-scale longitudinal population study in the UK found that children of fathers who were postnatally depressed had an increased risk of conduct problems and hyperactivity at age 3.5, even after controlling for maternal depression and socioeconomic factors [27].…”
Section: Introductionmentioning
confidence: 96%
“…There is evidence to suggest that paternal psychological functioning, including depression and stress, is associated with externalising child behavior problems that can originate very early in development [23][24][25][26]. For example, a recent large-scale longitudinal population study in the UK found that children of fathers who were postnatally depressed had an increased risk of conduct problems and hyperactivity at age 3.5, even after controlling for maternal depression and socioeconomic factors [27].…”
Section: Introductionmentioning
confidence: 96%
“…Finally, we considered only those studies examining children in the age range of two to eighteen, as our child outcomes of interest (externalizing and internalizing problems) cannot be appropriately diagnosed or reliably assessed in children younger than two, and we defined children as individuals younger than 18 years of age. From the original 121 studies identified, 17 met the above-described inclusion criteria (i.e., Brody, Kim, Murray, & Brown, 2004;Chi & Hinshaw, 2002;Conger, Patterson, & Ge, 1995;Conger et al, 1992;Conger et al, 1993;DeGarmo, Patterson, & Forgatch, 2004;Dumas & Serketich, 1994;Fendrich, Warner, & Weissman, 1990;Frye & Garber, 2005;Hammen et al, 2004;Herwig, Wirtz, & Bengel, 2004;Jaser et al, 2005;Kim & Brody, 2005;Low & Stocker, 2005;Marchand & Hock, 1998;Nelson, Hammen, Brennan, & Ullman, 2003;Panaccione & Wahler, 1986).…”
Section: Criteria For Inclusionmentioning
confidence: 99%
“…The expression of depressive symptoms can interfere with parents' abilities to be nurturing, to show firm and consistent discipline, and to avoid "giving in" to child tantrums through negative reinforcement (Lovejoy et al 2000;Marchand and Hock 1998). We propose that the presence of parental depressive symptoms interferes with parental behavior and is reflected in a lack of nurturance, rejection of the child, and poor monitoring and that these behaviors, in turn, contribute to child maladjustment.…”
mentioning
confidence: 93%